Complications of Tonsillectomy in Adults: Tonsillectomy complications - Hoque, Farzana; Chowdhury, M Alamgir; Shumon, Ahmed Minhaz; Yasmeen, Naseem; Md Jamil, Abu Naser; Barua, Raju (Journal of the Medical College for Women & Hospital, 2024)
Background: Tonsillectomy is a very common surgery performed by Ear Nose Throat (ENT) surgeons. There are different methods of tonsillectomy .A number of different complications are related to this surgery. Objective: To find out the complications of tonsillectomy by dissection method. Materials and Method: It was a prospective study carried out in the department of ENT, Medical College for Women and Hospital, Uttara, for a period of six months, from 1st July to 31st December 2023. Only patients admitted for tonsillectomy by dissection method were included in the study. Patients of tonsillitis with enlarged adenoids and other oral pathologies were excluded from this study. Data was collected using pre-designed data collection sheet. Data was processed and analyzed using SPSS software program, version 29 for windows. Results: This study showed that there was a preponderance of female patients (61.43%), with maximum patients being in the age group of 21-40 years (52.85%). On the 7th post operative day (POD), throat pain was the main complaint (48.57%), compared to 1st POD where dysphagia predominated (34.28%). Conclusion: This study aimed at finding out the different complications of tonsillectomy by dissection method, including parameters like patient factors, time taken by different types of surgeons to perform the surgery. This would help surgeons to become more efficient so as to guide the future ENT surgeons and to minimize the complications for better patient compliance. J Med Coll Women Hosp. 2024; 20(2): 64-71